Convergence to efficiency in FTSE-100 futures market. (2nd August 2010) - Lien, Donald; Xiang, Ju
We conduct efficiency test using the conventional method in Chordia et al. (2005) and the wavelet analysis. For the FTSE-100 futures data from January 2001 through December 2004, both approaches identify that, conditional on order imbalance, it takes about ten minutes for the market to converge to efficiency, which is shorter than the 30-minute required for large US stocks. Similar to the stock market case, the conventional method produces a longer-term moment puzzle that short-term (ten-minute) unpredictability cannot prevent a longer-term (30-minute) return momentum. This puzzle is resolved when the wavelet analysis is applied.